2019
DOI: 10.3389/frai.2019.00021
|View full text |Cite
|
Sign up to set email alerts
|

Volume Prediction With Neural Networks

Abstract: Changes in intraday trading volume are integral to any algorithmic trading strategy. Accordingly, forecasting the change in trading volume is paramount to better understanding the financial markets. This paper introduces a new method to forecast the log change in trading volume, leveraging the power of Long Short Term Memory (LSTM) networks in conjunction with Support Vector Regression (SVR) and Autoregressive (AR) models. We show that LSTM contributes to a more accurate forecast, particularly when constructed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…Because of the noisy fluctuations existed in the trading data, it is a desirable ability to incorporate longterm information to alleviate the short-term noise. In contrast with the previous work [Libman et al, 2019], which views the price and volume data as a whole and feeds them into a neural network to get a mixed representation, we argue that there is a heterogeneity gap between price data and volume data, therefore we separately process price data and volume data as price-graph and volume-graph. Each layer of our short-term fluctuation module consists of two parts, aggregation step and update step.…”
Section: Short-term Fluctuation Modelingmentioning
confidence: 85%
See 3 more Smart Citations
“…Because of the noisy fluctuations existed in the trading data, it is a desirable ability to incorporate longterm information to alleviate the short-term noise. In contrast with the previous work [Libman et al, 2019], which views the price and volume data as a whole and feeds them into a neural network to get a mixed representation, we argue that there is a heterogeneity gap between price data and volume data, therefore we separately process price data and volume data as price-graph and volume-graph. Each layer of our short-term fluctuation module consists of two parts, aggregation step and update step.…”
Section: Short-term Fluctuation Modelingmentioning
confidence: 85%
“…Trading volume movement prediction aims to predict the volume in a certain period of time based on stock market information, which is crucial to a variety of financial applications, e.g., stock market anomaly detection, risk management and algorithmic trading [Brownlees et al, 2010;Libman et al, 2019]. More importantly, when investors try to buy/sell large quantities of stocks, the order itself will instantaneously drive the stock price to the undesirable direction (i.e., higher price for a buy order and lower price for a sell order) and thus the total cost for the execution will be very expensive [Ye et al, 2014].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…We utilize Deep Feed Forward Neural Networks for our forecasting algorithm. Deep learning has been steadily growing in popularity, especially in academic studies, which have shown successful applications of deep learning algorithms in a variety of settings (see for example, Libman et al, 2019 ). Despite this, papers researching applications of deep learning methods to the financial markets are often recent and few in number.…”
Section: Introductionmentioning
confidence: 99%